Competitiveness of Coal Chemical Industry Based on Diamond Model. (17th August 2022) - Song, Meihui; Wang, Weicai; Sun, Shuoheng
Abstract : Coal chemical industry is one of the main ways of clean coal utilization. The orderly and regulated development of coal chemical industry is an important task in supply-side reform of China's coal industry. China's coal chemical industry has a good development foundation and great potentials and has taken the lead in some fields globally. Based on the six elements of the diamond model and qualitative analysis, an evaluation index system is constructed. The weights of different indexes are obtained through the entropy weight method, and the influence of the six elements on the competitiveness of the coal chemical industry is analyzed. The results show that among the six elements of the diamond model, horizontal competition delivers the greatest impact on the competitiveness of the coal chemical industry, followed by production factors, related and supportive industries, and the government, with demand conditions showing the least impact on the competitiveness of this industry.